Osoba i wolność w myśli Pierre'a Teilharda de Chardina - Rogacz, Dawid (My University, 2013)
The idea of freedom in the thought of Pierre Teilhard de Chardin has not already been analysed. This paper delves into this issue in four dimensions: ontological, anthropological, social and theological. The concept of spirit as unifying direction of evolution of the universe and the notion of radial energy guarantee the ontological possibility of freedom. Human person is different from other beings because of her consciousness of his own freedom. Specific embodiments of this freedom are love and work; freedom should not be confused with “the will to live”. Unification and development of the mankind are main social consequences of freedom. God is the ultimate cause and the purpose of freedom, because the love of God is the most complete incentive to make an effort.
Keywords: Teilhard de Chardin; wolność; personalizm; filozofia francuska